Respuesta :
Answer
[tex]x=28[/tex]
[tex]y=32[/tex]
Explanation
Let's solve each equation step by step
Equation 1: [tex]\frac{3}{4} (x-12)=12[/tex]
Step 1. Distribute [tex]\frac{3}{4}[/tex]
[tex]\frac{3}{4} x-\frac{3}{4} *12=12[/tex]
[tex]\frac{3}{4} x-9=12[/tex]
Step 2. Add 9 to both sides
[tex]\frac{3}{4} x-9+9=12+9[/tex]
[tex]\frac{3}{4} x=21[/tex]
Step 3. Multiply both sides of the equation by [tex]\frac{4}{3}[/tex]
[tex]\frac{3}{4} x*\frac{4}{3}=21*\frac{4}{3}[/tex]
[tex]x=28[/tex]
Equation 2: [tex]\frac{3}{4} y-12=12[/tex]
Step 1. Add 12 to both sides
[tex]\frac{3}{4} y-12+12=12+12[/tex]
[tex]\frac{3}{4} y=24[/tex]
Step 2. Multiply both sides by [tex]\frac{4}{3}[/tex]
[tex]\frac{3}{4} y*\frac{4}{3}= 24*\frac{4}{3}[/tex]
[tex]y=32[/tex]
Answer:
The required value of x = 28
The required value of y = 32
Step-by-step explanation:
The given two equations are :
[tex]\frac{3}{4}(x-12)=12..........(1)\\\\\frac{3}{4}\cdot y-12=12...........(2)[/tex]
Now, we need to solve both the equations and find out the required values of both the unknowns x and y.
Solving equation (1) to obtain value of x. We have,
[tex]\frac{3}{4}(x-12)=12\\\\\text{On cross multiplication, we get}\\\\\implies 3\times (x-12)=12\times 4\\\implies 3x -36=48\\\implies 3x=48+36\\\implies 3x=84\\\bf\implies x=28[/tex]
Solving equation (2) to obtain value of y. We have,
[tex]\frac{3}{4}\cdot y-12=12\\\\\implies \frac{3}{4}\cdot y=12+12\\\\\implies \frac{3}{4}\cdot y=24\\\\\text{On cross multiplicatrion, We get}\\\implies 3\cdot y=24\times 4\\\implies 3y = 96\\\bf\implies y=32[/tex]
Hence, The required value of x = 28
And The value of y = 32